2022
DOI: 10.1093/brain/awac333
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of 10 plasma phospho-tau assays in prodromal Alzheimer’s disease

Abstract: Plasma phospho-tau (p-tau) species have emerged as the most promising blood-based biomarkers of Alzheimer's disease. Here, we performed a head-to-head comparison of p-tau181, p-tau217 and p-tau231 measured using 10 assays to detect abnormal brain amyloid-β status and predict future progression to Alzheimer's dementia. The study included 135 patients with baseline diagnosis of mild cognitive impairment (mean age 72.4 years; 60.7% women) who were followed for an average of 4.9 years. Seventy-one participants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
224
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 179 publications
(246 citation statements)
references
References 35 publications
18
224
4
Order By: Relevance
“…The amyloid-β (Aβ)42/40 ratio in blood plasma has turned out to represent a highly attractive and robust peripheral biomarker of the cerebral amyloid pathology associated with Alzheimer’s disease (AD) [ 1 5 ]. Furthermore, a number of recent studies have shown that also the plasma concentrations of specific phosphorylated forms of tau protein, namely p-tau181, ptau217 and ptau231, can reliably detect an abnormal brain Aβ status as indicated by Aβ-positron emission tomography (Aβ-PET) or low CSF Aβ42/40 [ 6 11 ]. Recently, the first plasma Aβ42/40 assay gained approval by the Centers for Medicare & Medicaid Services under the Clinical Laboratory Improvement Amendments (CLIA) protocol [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid-β (Aβ)42/40 ratio in blood plasma has turned out to represent a highly attractive and robust peripheral biomarker of the cerebral amyloid pathology associated with Alzheimer’s disease (AD) [ 1 5 ]. Furthermore, a number of recent studies have shown that also the plasma concentrations of specific phosphorylated forms of tau protein, namely p-tau181, ptau217 and ptau231, can reliably detect an abnormal brain Aβ status as indicated by Aβ-positron emission tomography (Aβ-PET) or low CSF Aβ42/40 [ 6 11 ]. Recently, the first plasma Aβ42/40 assay gained approval by the Centers for Medicare & Medicaid Services under the Clinical Laboratory Improvement Amendments (CLIA) protocol [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Similarly, previous comparisons between multiple species and assays of p-tau measures showed only a modest correlation, suggesting also significantly different diagnostic performance. 11,22 Considering the differences in clinical performance of different assays for the same biomarkers, importance the use of high-performing assays is of utmost when comparing different biomarkers to avoid reporting differences that are related to the method rather than the biomarkers themselves.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is very important, and we advocate minimizing the false detection of a pathological situation in patients by always combining plasma P-Tau181 with an assessment of renal function, e.g., through creatinine measurement and GFR estimation. This recommendation should be confirmed for other P-Tau isoforms (P-Tau217, P-Tau231) measured by immunoassay 25 or mass spectrometry 30 . The clearance of P-Tau by the kidney will have to be studied in more detail, taking into account our knowledge of the urinary excretion of protein in physiological and pathological conditions 31 and the very small amounts of this biomarker detected so far in the urine in free form 32 or associated with exosomes 33 .…”
Section: Discussionmentioning
confidence: 93%
“…We advocate minimizing the false detection of a pathological situation in patients by always combining plasma P-Tau181 with an assessment of renal function, e.g., through creatinine measurement and GFR estimation. This recommendation should be confirmed for other P-Tau isoforms (P-Tau217, P-Tau231) measured by immunoassay 25 or mass spectrometry 30 . We cannot exclude at this stage that altered renal function may also contribute in some way to the progression of AD.…”
Section: Discussionmentioning
confidence: 93%